"Intercellular bridges" in a case of well differentiated squamous carcinoma. Issue 2 (17th December 2015) - Nguyen, Michaela; Mikita, Geoffrey; Hoda, Rana S.
Abstract: Intercellular bridges may aide in definitive identification of malignant cell origin, especially in squamous cell carcinoma. They are difficult to identify in routine cytologic specimens and are especially rare in smear preparations. Herein, we present images of intercellular bridges from a case of well differentiated squamous cell carcinoma of the esophagus in a cytologic specimen obtained from FNA of a paraesophageal lymph node. Diagn. Cytopathol. 2016;44:121–123. © 2015 Wiley Periodicals, Inc.